Inhibition of nuclear factor-kappaB, cyclooxygenase-2, and metalloproteinase-9 expression by flavanols from evening primrose (Oenothera paradoxa) in human colon cancer SW-480 cells. (October 2017) - Owczarek, Katarzyna; Hrabec, Elżbieta; Fichna, Jakub; Sosnowska, Dorota; Koziołkiewicz, Maria; Szymański, Jacek; Lewandowska, Urszula
Graphical abstract: Highlights: Evening primrose flavanol preparation (EPFP) inhibits SW-480 cell viability. EPFP reduces NF-κB protein expression and phosphorylation of its p65 subunit in those cells. EPFP down-regulates both protein and mRNA expression of COX-2 in those cells. EPFP inhibits MMP-9 protein synthesis and secretion to the culture medium by the SW-480 cells. Abstract: The present study examines the chemical composition of an evening primrose flavanol preparation (EPFP) and its chemopreventive activity in colon cancer SW-480 cells. EPFP was found to inhibit SW-480 cell viability by 67% vs. controls at 150 µM catechin equivalents (CE) following 72 h incubation (IC50  = 65 µM CE). EPFP decreased both NF-κB protein expression (33% vs. control at 100 µM CE) and phosphorylation at serine 529 of the p65 subunit (49% vs. control at 100 µM CE) in SW-480 cells. Moreover, 100 µM CE EPFP suppressed COX-2 mRNA expression to 23% of control values and protein expression to 78%. In addition, EPFP reduced MMP-9 protein expression to 24% vs. controls at 100 µM CE. These results provide the first evidence that EPFP reduces NF-κB, COX-2, and MMP-9 expression, which may suggest it has cytotoxic, anti-inflammatory, and anti-metastatic activities towards colon cancer cells.